Faktor-Faktor yang Mempengaruhi Keikutsertaan Ibu dalam Pemberian Imunisasi Measles Rubella pada Bayi Usia 9-12 Bulan di Wilayah Kerja Puskesmas Rantau Panjang - Habibah Habibah; Vip Paramarta; Rulia Rulia (Jurnal Akademika Baiturrahim Jambi, 2026)
Mothers play a crucial role in achieving child immunization coverage. This study aims to analyze the factors influencing maternal participation in the administration of the Measles-Rubella (MR) vaccine for infants aged 9–12 months in the working area of Rantau Panjang Public Health Center. This is a quantitative study with a cross-sectional design, employing descriptive and verification methods. The population consisted of 283 mothers with children under two years old (BADUTA), and a sample of 74 respondents was selected using accidental sampling and the Slovin formula. The results show that maternal knowledge significantly influences participation in MR immunization (72.7%), as well as maternal behavior (59.8%) and support from healthcare workers (67.1%). Maternal education also has an effect (26.8%). However, family support and maternal age do not significantly influence participation. Simultaneously, knowledge, behavior, family support, healthcare support, age, and education contribute to a 71.3% influence on maternal participation in MR immunization. It is recommended that the Rantau Panjang Public Health Center enhance education for mothers regarding the importance of MR immunization through regular counseling sessions, visual media, and direct, easy-to-understand approaches. Effective education is expected to improve MR immunization coverage and support the national immunization program